2002
DOI: 10.2307/3666223
|View full text |Cite
|
Sign up to set email alerts
|

How Does Strategic Competition Affect Firm Values? A Study of New Product Announcements

Abstract: We examine the role of strategic interaction in explaining the valuation effect of new product announcements and employ Sundaram, John, and John's (1996) competitive strategy measure to operationalize the nature of a firm's competitive interaction. Using a sample of new product introductions between 1991 and 1995, we find that the market values introductions announced by firms in strategic substitutes competition more favorably than those announced by firms in strategic complements competition. These results h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 44 publications
(95 reference statements)
12
90
0
Order By: Relevance
“…Building on the work of Sundaram et al (1996), Chen et al (2002) provide further support for the effect of announcements on the stock price of disrupted firms. Employing a dataset of 384 new product announcements by firms from 39 industries, they found that where a new product launch announcement was viewed as a strategic substitute for an incumbent product, the incumbent experienced negative and statistically significant reductions in its stock market value within a narrow 2-day window.…”
Section: Importance Of the Put Option Relative To The Dcfmentioning
confidence: 81%
See 3 more Smart Citations
“…Building on the work of Sundaram et al (1996), Chen et al (2002) provide further support for the effect of announcements on the stock price of disrupted firms. Employing a dataset of 384 new product announcements by firms from 39 industries, they found that where a new product launch announcement was viewed as a strategic substitute for an incumbent product, the incumbent experienced negative and statistically significant reductions in its stock market value within a narrow 2-day window.…”
Section: Importance Of the Put Option Relative To The Dcfmentioning
confidence: 81%
“…Such price behaviour is justified from theory considerations (Arrow, 1962). This is reinforced by empirical studies which have observed the negative impact upon an incumbent's market value that an announcement of disruptive innovations from rivals (Sundaram et al, 1996), or the actual launch of rival products that are strategic substitutes of the incumbent's products (Chen et al, 2002;Whinston and Collins, 1992).…”
Section: The Assumptionsmentioning
confidence: 97%
See 2 more Smart Citations
“…al, 19955;Chen et. al., 2002;Sharma and Lacey, 2004;Cho and Pucik, 2005;Connolly and Hirschey, 2005).…”
Section: Introductionmentioning
confidence: 99%